Fertilización tardía y establecimiento de Quercus ilex subsp. ballota 2/11 - CORTINA, J.; MONERRIS, J.; DISANTE, K.; FUENTES, D.; VALDECANTOS, A. (V Congreso Forestal Español, 2009)
La restauración de ecosistemas mediterráneos con frecuencia requiere la reintroducción de especies leñosas. Pero existe una gran incertidumbre sobre las características que debe reunir un brinzal para aumentar sus probabilidades de éxito en el campo. Algunos estudios han mostrado que la fertilización en vivero permite una mayor supervivencia y crecimiento en campo. Sin embargo, en estos experimentos, las variaciones en el estado nutricional no se pueden desligar de los cambios morfológicos que promueve la fertilización. Para evaluar la importancia del estado nutricional, frente a las variaciones morfológicas inducidas por éste, hemos evaluado el comportamiento en el campo de brinzales de una savia de Quercus ilex subsp. ballota no fertilizados y brinzales a los que se aplicó fertilización tardía (posterior a la parada otoñal de crecimiento de la parte aérea). Nuestras hipótesis son: (i) la fertilización tardía permite mejorar el estado nutricional de los brinzales sin variar su tamaño y (ii) con ello, se aumenta la supervivencia y el crecimiento de los brinzales en el campo. La fertilización tardía no afectó al tamaño de los brinzales, pero mejoró su estado nutricional. En campo, la supervivencia fue muy elevada antes del primer verano (>98%), disminuyendo después del mismo hasta un rango de valores de 65-100%. En ningún caso la supervivencia estuvo relacionada con la fertilización en vivero. Por el contrario, la tasa de crecimiento antes del verano fue inferior en plantas no fertilizadas, invirtiéndose esta tendencia durante el verano. La tasa anual de crecimiento fue superior en las plantas fertilizadas, confirmando parcialmente nuestra hipótesis. La fertilización tardía representa una técnica sencilla para reducir el uso de fertilizantes en vivero, produciendo brinzales de pequeño tamaño pero elevada capacidad de respuesta en campo. Palabras
The following values have no corresponding Zotero field: periodical: V Congreso Forestal Español pub-location: Avila
Keywords: cultivo en vivero; encinares; estado nutricional; Quercus rotundifolia; restauración forestal

Seedling performance in sewage sludge-amended degraded Mediterranean woodlands - FUENTES, D.; Valdecantos, a; CORTINA, J.; Vallejo, V. R. R. (Ecological Engineering, 2007)
Biosolids have been widely used for land reclamation, but information on their use in restoration, i.e., on less degraded areas, is scarce. Biosolids may be used to restore forest ecosystems by fostering tree establishment in degraded shrublands. Detailed knowledge on the effects of biosolid application is needed to optimize such practice. We evaluated the effect of different rates (0, 7.5 and 14.5 kg dry weight per plant) and types of biosolid application on the performance of Pinus halepensis and Quercus ilex seedlings, and operational costs. Biosolids increased seedling mortality in both species, particularly when seedlings were planted in direct contact with them. Mortality mostly occurred during the ﬁrst year, and was probably favored by soil shrinking and salinity. Foliar and needle nitrogen concentration increased with biosolid rate in the short term, but biosolids affected negatively (P. halepensis), or had no effect (Q. ilex) on phosphorus and potassium concentration. Biosolids had a positive effect on P. halepensis growth, and a negative effect on Q. ilex growth at the highest rate when seedlings were in contact with biosolids. Cost of this type of biosolid application approximately doubled plantation cost, but were similar or cheaper that landﬁll disposal of biosolids. The lowest application rate showed the best balance between seedling response and costs for P. halepensis, whereas biosolid use cannot be recommended for Q. ilex.
Keywords: mortality; Pinus halepensis; Quercus ilex; Restoration; Salinity; seedling growth; Sewage sludge

Seedling performance in sewage sludge-amended degraded Mediterranean woodlands - FUENTES, D.; VALDECANTOS, A.; CORTINA, J.; Vallejo, V.R. R (Ecological Engineering, 2007)
Biosolids have been widely used for land reclamation, but information on their use in restoration, i.e., on less degraded areas, is scarce. Biosolids may be used to restore forest ecosystems by fostering tree establishment in degraded shrublands. Detailed knowledge on the effects of biosolid application is needed to optimize such practice. We evaluated the effect of different rates (0, 7.5 and 14.5 kg dry weight per plant) and types of biosolid application on the performance of Pinus halepensis and Quercus ilex seedlings, and operational costs. Biosolids increased seedling mortality in both species, particularly when seedlings were planted in direct contact with them. Mortality mostly occurred during the ﬁrst year, and was probably favored by soil shrinking and salinity. Foliar and needle nitrogen concentration increased with biosolid rate in the short term, but biosolids affected negatively (P. halepensis), or had no effect (Q. ilex) on phosphorus and potassium concentration. Biosolids had a positive effect on P. halepensis growth, and a negative effect on Q. ilex growth at the highest rate when seedlings were in contact with biosolids. Cost of this type of biosolid application approximately doubled plantation cost, but were similar or cheaper that landﬁll disposal of biosolids. The lowest application rate showed the best balance between seedling response and costs for P. halepensis, whereas biosolid use cannot be recommended for Q. ilex.
Keywords: mortality; Pinus halepensis; Quercus ilex; Restoration; Salinity; seedling growth; Sewage sludge